Growth, mortality and recruitment of planktonic shrimp, Acetes intermedius in the coastal waters of Bintulu, Sarawak East Malaysia. - Saini, Masitah; Arshad, Aziz; Nurul Amin, Sanker Mohammad; Idris, Mohd Hanafi (Academic Journals, 2011)
Growth, mortalities (natural and fishing) recruitment percentage and exploitation status of Acetes intermedius were examined of samples collected from the coastal waters of Bintulu, Sarawak between January and December 2009. Monthly length frequency data were analyzed using FiSAT software for estimating population parameters, including asymptotic length (L∝), growth co-efficient (K) and exploitation rate (E) to assess the status of the stock. The asymptotic length (L∝) and growth co-efficient (K) was estimated as 43.05 mm and 1.90 yr-1. The maximum life span (tmax) A. intermedius was estimated at 1.58 yr-1. Total mortality (Z) was estimated at 4.68 yr-1. The rate of natural mortality (M) and fishing mortality was calculated as 2.49 yr-1 and 2.195 yr-1, respectively. The recruitment pattern of A. intermedius was continuous throughout the year with two major peaks. The exploitation rate (E) was estimated at 0.47 during the study period. The exploitation rate was slightly below the optimum level of exploitation (E = 0.50) and the condition of the stock is still under-fishing status.